Improving poverty reduction in Europe: What works best where? - Chrysa Leventi; Holly Sutherland; Iva Valentinova Tasseva (University of Essex, Institute for Social and Economic Research (ISER), 2017)
We provide evidence of the relative cost-effectiveness of different types of policy instrument in reducing poverty or limiting its increase, comparing within and between seven diverse EU countries. We do that by measuring the implications of increasing/reducing the instrument size within its national context, using microsimulation methods. We consider commonly-applied policy instruments with a direct effect on household income: child benefits, minimum income components of social assistance, income tax lower thresholds and minimum wages and a benchmark case of changing the size of the whole tax-benefit system. We find that the assessment of the most cost effective instrument may depend on the measure of poverty used and the direction and scale of the change. Nevertheless, our results indicate that the options that reduce poverty most cost-effectively in most countries are increasing child benefits and social assistance while reducing the former is a particularly poverty-increasing way of making budgetary cuts.
Keywords: D13; D30; H53; I38; 330; Poverty; EU; social policy; fiscal policy; microsimulation